Pengembangan Objek Wisata Pantai Tanjung Papuma Dalam Meningkatkan Pendapatan Masyarakat Pesisir (Studi pada Kantor Pariwisata Kabupaten Jember dan Perum Perhutani Unit II Jawa Timur) - Yuana, Wella Oky Candra (Jurnal Administrasi Publik, 2015)
Abstract: The Development of Tanjung Papuma Beach Tourism Object to Improve The Income of Coastal Community (Study at Tourism Office of Jember Regency and Perum Perhutani Unit II of East Java). Tourism is a strategic sector which is designated as the leading sector to support national development. Recalling the importance of tourism, therefore, tourism must be planned and developed properly to optimize its utilization to the community. Being as a marine country with sea-based natural resources, Indonesia is enriched with marine potentials but without eliminating its land potentials. One tourism object is Tanjung Papuma Beach Tourism Object. The result of this study can be concluded the potentials owned by Tanjung Papuma Beach Tourism Object are concerned with its geographical site, tourism object attraction, and number of tourist visit that always increases every year. The development of Papuma Tanjung Beach Tourism Object has been attempted by related parties including Tourism Office of Jember Regency and Perum Perhutani Unit II of East Java, and immediate community by providing the necessary structures and infrastructures of Tanjung Papuma Beach Tourism Object, developing tourism object attraction, improving tourism activity and promotion, and increasing community participation. The development of tourism object will give big impact on immediate community because the community always has opportunity to exploit tourism potentials in order to create new employment which then influences the improvement of the income of coastal commuity. There are factors supporting and constraining Tanjung Papuma Beach Tourism Object. The supporting factors are the potentials of Tanjung Papuma Beach Tourism Object, for the same purpose, and the rule between the management of tourism object and community. The constraining factors include less responsive leaders in Perum Perhutani, quite stronger economic principle, and lower human resource in the management of tourism object or in the immediate community. It is suggested that both intervention and support of all managerial elements in tourism object are needed to develop good cooperation. Â  Keywords: tourism development, income of coastal community Abstrak: Pengembangan Objek Wisata Pantai Tanjung Papuma Dalam Meningkatkan Pendapatan Masyarakat Pesisir (Studi pada Kantor Pariwisata Kabupaten Jember dan Perum Perhutani Unit II Jawa Timur). Pariwisata merupakan sektor strategis pada suatu negara dalam hal untuk menunjang dan memajukan pembangunan. Mengingat begitu pentingnya peran pariwisata maka dibutuhkan upaya pengembangan pariwisata yang terencana agar bermanfaat bagi masyarakat. Sebagai negara maritim kekayaan alam berbasis bahari berpotensi tinggi untuk dikembangkan tanpa menghilangkan potensi yang ada di daratan. Salah satu objek wisata yang perlu dikembangkan adalah objek wisata Pantai Tanjung Papuma. Hasil penelitian menunjukkan bahwa bahwa potensi yang dimiliki objek wisata Pantai Tanjung Papuma dapat dilihat dari letak geografis, daya tarik objek wisata, dan kunjungan wisatawan. Pengembangan objek wisata Pantai Tanjung Papuma dilakukan oleh Kantor Pariwisata Kabupaten Jember, Perum Perhutani Unit II Jawa Timur serta masyarakat setempat dengan cara penyediaan sarana dan prasarana objek wisata Pantai Tanjung Papuma, pengembangan objek dan daya tarik wisata, promosi wisata, dan peningkatan peran masyarakat. Adanya pengembangan objek wisata tersebut, dapat memberikan dampak yang besar bagi masyarakat setempat yaitu tercipta lapangan kerja baru yang berpengaruh pada peningkatan pendapatan masyarakat pesisir. Dalam pengembangan objek wisata Pantai Tanjung Papuma terdapat faktor pendukung dan faktor penghambat. Faktor pendukung diantaranya potensi yang dimiliki objek wisata Pantai Tanjung Papuma, adanya tujuan yang sama, serta peran antara pengelola objek wisata dan masyarakat sekitar. Faktor penghambat pengembangan objek wisata yaitu pimpinan dari Perum Perhutani yang kurang tanggap, adanya prinsip ekonomi yang kuat dan kualitas sumber daya manusia yang masih rendah. Hal ini perlunya campur tangan dan dukungan dari semua pihak pengelola objek wisata agar tercipta kerjasama yang baik. Â  Kata kunci: pengembangan wisata, pendapatan masyarakat pesisir